Towards Sustainable Manufacturing Through Packaging Customization: A Case Study Based on The Joinery Manufacturing Company - Paweł POSADZY; Fredrick MUMALI (Communications of International Proceedings, 2021)
Reducing the carbon footprint in manufacturing operations is becoming more and more critical. While enterprises continue to adopt various sustainability strategies in manufacturing, such as energy efficiency and zero-net emissions, petroleum-based plastic products such as Styrofoam continue to be utilized as standard packaging materials in the joinery sector with no clear disposal strategies for most consumers. The study seeks to evaluate packaging customization in reducing the demand for petroleum-based plastic products that constitute standard packaging materials. The research aims to showcase that adopting customized and non-carbon-based packaging materials in the joinery sector alleviates the disposal of standard packaging materials such as Styrofoam by lowering their demand and presence in the supply chain. The study adopts a case study description involving a manufacturing entity in the joinery industry focus. The demand for plastic-based materials such as Styrofoam in the supply chain is evaluated in standard and customized packaging approaches.  The analysis reveals a reduction in the demand for plastic-based materials when a customized packaging approach is used. As a result, the amount of Styrofoam and other plastic materials that reach the end-users in packaging materials is significantly reduced. Thus, customized packaging in the joinery industry, instead of the standard approach, reduce petroleum-based plastic components in the supply chain, contributing to zero-carbon as critical sustainable manufacturing strategies.
Keywords: Sustainable Manufacturing; Customized Packaging.